Fabrication of Three‐Dimensional Net‐Structured Polyvinyl Alcohol Nanofibers Using Spray‐Freeze‐Drying Technique - Abdur Razzaque; Motoki Katsumi; Riku Shimokawa; Md. Shakhawat Hossain; Koji Nakane (Nano Select, 2025)
ABSTRACT Polyvinyl alcohol (PVA) nanofibers have potential importance in industrial applications. In this study, three‐dimensional (3D) net‐structured PVA nanofibers are successfully fabricated using the spray‐freeze‐drying (SFD) technique for the first time. At first, different concentrations of PVA solutions from 0.001 to 5 wt% are applied to prepare PVA nanofibers using liquid nitrogen at −196°C by the SFD method. These nanofibers are characterized by scanning electron microscopy for morphological analysis, photo ruler software for diameter measurement, thermogravimetric analysis and differential scanning calorimetry for thermal stability and crystallinity, as well as nitrogen adsorption isotherms and pore size distribution curves for specific surface area and porous surface quality. Prepared SFD nanofibers with finer nano diameters, fewer beads, more regular 3D net‐structures and without any massive blocks are obtained from 0.05 to 1 wt%. These are compared with the nanofibers prepared by the freeze‐drying (FD) technique. The SFD method shows better results than the FD method in respect to fiber morphology, finer nanoscale diameter, crystallinity, specific surface area, and surface porous property. The best results are obtained from the nanofibers fabricated by the SFD method at 0.1 wt% concentration. Finally, the findings of this work open the opportunities for potential industrial applications and further development of PVA nanofibers.